Adhesive laminated core for stator and rotating electric machine
By employing an adhesive structure with varying adhesive strengths between the tooth and core back portions, the adhesive laminated core for a stator achieves enhanced mechanical strength without compromising magnetic properties, addressing the limitations of existing technologies.
Patent Information
- Application Number
- JP2022192094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-17
- Filing Date
- 2022-11-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2039-12-17
AI Technical Summary
Existing adhesive laminated cores for stators face challenges in achieving mechanical strength without compromising the magnetic properties of the teeth, particularly due to high adhesive strength in tooth portions leading to adverse effects on magnetic properties.
The adhesive laminated core for a stator employs a unique adhesive structure where the adhesive strength in the tooth portion is intentionally lower than in the core back portion, using adhesives with different chemical components, and maintaining an adhesive strength ratio between 0.1 and 1.0 at room temperature.
This approach enhances the mechanical strength of the stator core while preserving the magnetic properties of the teeth, thereby improving the overall performance of the rotating electric machine.
Smart Images

Figure 0007657191000007 
Figure 0007657191000008 
Figure 0007657191000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive laminated core for a stator and a rotating electric machine. This application claims priority based on Japanese Patent Application No. 2018-235863, filed on December 17, 2018, the contents of which are incorporated herein by reference. [Background technology]
[0002] In the laminated core used in a motor, when the thickness of the electromagnetic steel sheets is reduced, the rigidity of each electromagnetic steel sheet is reduced. Therefore, although the number of laminated sheets increases, the rigidity of the laminated core as a whole is also reduced. In this case, there is a risk that the stator will deform or the laminated core will become misaligned as the rotor rotates during operation of the motor. In addition, an increase in the number of laminated sheets makes handling difficult during the manufacturing of the laminated core, which can cause problems such as deformation of the laminated core and difficulty in winding processing.
[0003] In response to such problems, the mechanical strength of the laminated core has been increased by fixing the shape of the laminated core with an adhesive, as in the motor core (laminated core) described in Patent Document 1 below. That is, in the motor core described in Patent Document 1, a room-temperature-curing instant adhesive layer is arranged in all teeth so as to extend along the direction in which the teeth extend (radial direction). In addition, a plurality of thermosetting organic adhesive layers are arranged along the circumferential direction of the substantially annular electromagnetic steel sheet. Adjacent electromagnetic steel sheets are bonded together by the room-temperature-curing instant adhesive layer and the thermosetting organic adhesive layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2016-171652 Summary of the Invention [Problem to be solved by the invention]
[0005] However, if the strength of the adhesive in the teeth is too high, the adhesive will shrink as it hardens, causing a compressive force on the teeth that will adversely affect their magnetic properties. The technology disclosed in Patent Document 1 does not recognize this problem, and naturally does not take any measures to solve it.
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide an adhesive laminated core for a stator having an adhesive structure that increases mechanical strength without adversely affecting the magnetic characteristics of the teeth portion, and a rotating electric machine equipped with this adhesive laminated core for a stator. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention employs the following means. (1) A stator bonded laminated core according to one aspect of the present invention comprises a plurality of electromagnetic steel sheets having a core back portion and teeth portions and stacked coaxially, and a plurality of bonding portions bonding the electromagnetic steel sheets at the core back portion and the teeth portions, respectively, and the bonding portions bond the electromagnetic steel sheets to each other at the core back portion and the teeth portions at room temperature of 20° C. to 30° C. In Each of the adhesive joints per unit area The partial adhesive strength is In Each of the adhesive joints per unit area Lower than partial adhesive strength, Core back part the adhesive portion in the tooth portion and the adhesive portion in the core-back portion are made of adhesives having different chemical components, and an average adhesive strength ratio obtained by dividing the partial adhesive strength in the tooth portion by the partial adhesive strength in the core-back portion at a room temperature of 20°C to 30°C is 0.1 or more. Less than 1.0 is within the range.
[0008] (2) In the aspect described in (1) above, the following configuration may be adopted: the adhesive portion is arranged on both the each tooth portion and the core back portion so as to overlap on each imaginary straight line connecting the widthwise center position of each tooth portion and the central axis of the electromagnetic steel sheet.
[0009] (3) In the aspect described in (1) above, the following configuration may be adopted: the adhesive portion is provided on all of the teeth portions, and the adhesive portion is provided at all positions of the core back portion adjacent to the radial outside of all of the teeth portions.
[0011] ( 4 ) In any one of the above aspects (1) to (3), the following configuration may be adopted: the average value S1 of the partial adhesive strength in the teeth portion is 1 to 15 MPa, the average value S2 of the partial adhesive strength in the core back portion is 15 to 50 MPa, and the average value S1 is lower than the average value S2.
[0013] ( 5 2) In any one of the above aspects (1) to (3), the following configuration may be adopted: the average thickness of each of the adhesive joints is 1.0 μm to 3.0 μm. ( 6 2) In any one of the above embodiments (1) to (3), the following configuration may be adopted: the average tensile modulus E of each of the adhesive joints is 1500 MPa to 4500 MPa. ( 7 ) In any one of the above embodiments (1) to (3), the following configuration may be adopted: each of the adhesive parts is an acrylic adhesive of room temperature adhesion type containing SGA made of an elastomer-containing acrylic adhesive.
[0014] ( 8 A rotating electric machine according to one aspect of the present invention includes the adhesive laminated core for a stator according to any one of (1) to (3) above. Effect of the Invention
[0015] According to each of the above aspects of the present invention, it is possible to provide an adhesive laminated core for a stator having an adhesive structure that increases mechanical strength while not adversely affecting the magnetic properties of the teeth portion, and a rotating electric machine equipped with this adhesive laminated core for a stator. [Brief description of the drawings]
[0016] [Figure 1] 1 is a cross-sectional view of a rotating electrical machine including a stator adhesive laminated core according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a side view of the stator bonded laminated core. [Diagram 3] 3 is a cross-sectional view taken along the line AA in FIG. 2, showing a plurality of examples of formation patterns of adhesive parts in the adhesive laminated core for a stator. FIG. [Figure 4] FIG. 2 is a side view of a manufacturing apparatus used to manufacture an embodiment of a stator bonded laminated core. [Diagram 5] FIG. 13 is a diagram illustrating the examples shown in Tables 1A and 1B, and is a graph illustrating the relationship between the partial adhesive strength at the teeth portion position and the partial adhesive strength at the core back portion position. [Figure 6] FIG. 13 is a diagram illustrating the examples shown in Tables 2A and 2B, and is a graph illustrating the relationship between the partial adhesive strength at the teeth portion position and the partial adhesive strength at the core back portion position. [Figure 7] FIG. 13 is a diagram illustrating the examples shown in Tables 3A and 3B, and is a graph illustrating the relationship between the partial adhesive strength at the teeth portion position and the partial adhesive strength at the core back portion position. [Figure 8] FIG. 13 is a diagram illustrating the examples shown in Tables 3A and 3B, and is a graph illustrating the relationship between the area ratio at the tooth portion position and the area ratio at the core back portion position. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, a stator adhesive laminated core according to one embodiment of the present invention and a rotating electric machine including this stator adhesive laminated core will be described with reference to the drawings. In this embodiment, the rotating electric machine will be described by taking an electric motor, specifically an AC electric motor, more specifically a synchronous electric motor, and even more specifically a permanent magnet field type electric motor, as an example. This type of electric motor is preferably used in, for example, electric vehicles.
[0018] 1, the rotating electric machine 10 includes a stator 20, a rotor 30, a case 50, and a rotating shaft 60. The stator 20 and the rotor 30 are housed in the case 50. The stator 20 is fixed within the case 50. In this embodiment, an inner rotor type rotating electric machine 10 is used in which the rotor 30 is located radially inside the stator 20. However, an outer rotor type rotating electric machine 10 in which the rotor 30 is located outside the stator 20 may also be used. Also, in this embodiment, the rotating electric machine 10 is a three-phase AC motor with 12 poles and 18 slots. However, the number of poles, the number of slots, the number of phases, etc. can be changed as appropriate. The rotating electric machine 10 can rotate at a rotation speed of 1000 rpm by applying an excitation current with an effective value of 10 A and a frequency of 100 Hz to each phase, for example.
[0019] The stator 20 includes a stator adhesive laminated core (hereinafter, stator core) 21 and a winding (not shown). The stator core 21 includes an annular core back portion 22 and a plurality of teeth portions 23. Hereinafter, the direction of the central axis O of the stator core 21 (or the core back portion 22) will be referred to as the axial direction, the radial direction of the stator core 21 (or the core back portion 22) (the direction perpendicular to the central axis O) will be referred to as the radial direction, and the circumferential direction of the stator core 21 (or the core back portion 22) (the direction going around the central axis O) will be referred to as the circumferential direction.
[0020] The core back portion 22 is formed in an annular shape when viewed in a plan view of the stator 20 in the axial direction. The multiple teeth portions 23 protrude radially inward from the inner circumference of the core back portion 22 (toward the central axis O of the core back portion 22 along the radial direction). The multiple teeth portions 23 are arranged at equal angular intervals in the circumferential direction. In this embodiment, 18 teeth portions 23 are provided at central angle intervals of 20 degrees centered on the central axis O. The multiple teeth portions 23 are formed to have the same shape and size as one another. Therefore, the multiple teeth portions 23 have the same thickness dimension as one another. The winding is wound around the teeth portion 23. The winding may be a concentrated winding or a distributed winding.
[0021] The rotor 30 is disposed radially inside the stator 20 (the stator core 21). The rotor 30 includes a rotor core 31 and a plurality of permanent magnets 32. The rotor core 31 is formed in an annular (circular) shape and is disposed coaxially with the stator 20. The rotating shaft 60 is disposed within the rotor core 31. The rotating shaft 60 is fixed to the rotor core 31. The multiple permanent magnets 32 are fixed to the rotor core 31. In this embodiment, a pair of the permanent magnets 32 forms one magnetic pole. The multiple pairs of permanent magnets 32 are arranged at equal angular intervals in the circumferential direction. In this embodiment, 12 pairs (24 in total) of permanent magnets 32 are provided at central angle intervals of 30 degrees around the central axis O.
[0022] In this embodiment, an embedded magnet type motor is used as the permanent magnet field type motor. A rotor core 31 is formed with a plurality of through holes 33 that pass through the rotor core 31 in the axial direction. The plurality of through holes 33 are provided corresponding to the arrangement of the plurality of permanent magnets 32. Each permanent magnet 32 is fixed to the rotor core 31 while being arranged in the corresponding through hole 33. Each permanent magnet 32 can be fixed to the rotor core 31 by, for example, bonding the outer surface of the permanent magnet 32 to the inner surface of the through hole 33 with an adhesive. Note that a surface magnet type motor may be used as the permanent magnet field type motor instead of the embedded magnet type.
[0023] Both the stator core 21 and the rotor core 31 are laminated cores. For example, the stator core 21 is formed by laminating a plurality of electromagnetic steel sheets 40 in a lamination direction, as shown in FIG. The lamination thickness (total length along the central axis O) of each of the stator core 21 and the rotor core 31 is, for example, 50.0 mm. The outer diameter of the stator core 21 is, for example, 250.0 mm. The inner diameter of the stator core 21 is, for example, 165.0 mm. The outer diameter of the rotor core 31 is, for example, 163.0 mm. The inner diameter of the rotor core 31 is, for example, 30.0 mm. However, these values are merely examples, and the lamination thickness, outer diameter, and inner diameter of the stator core 21 and the lamination thickness, outer diameter, and inner diameter of the rotor core 31 are not limited to these values. Here, the inner diameter of the stator core 21 is based on the tip end of the teeth portion 23 of the stator core 21. In other words, the inner diameter of the stator core 21 is the diameter of an imaginary circle inscribed in the tip end of all the teeth portion 23.
[0024] Each of the electromagnetic steel sheets 40 forming the stator core 21 and the rotor core 31 is formed, for example, by punching an electromagnetic steel sheet as a base material. A known electromagnetic steel sheet can be used as the electromagnetic steel sheet 40. The chemical composition of the electromagnetic steel sheet 40 contains 2.5% to 3.9% Si, as shown below in mass %. Elements other than Si are not particularly limited, but preferable ranges in this embodiment are clearly shown below. By setting the chemical composition within this range, the yield strength YP of each of the electromagnetic steel sheets 40 can be set to 380 MPa or more and 540 MPa or less.
[0025] Silicon: 2.5% to 3.9% Al: 0.001% to 3.0% Mn: 0.05% to 5.0% Remainder: Fe and impurities
[0026] In this embodiment, a non-oriented electromagnetic steel sheet is used as the electromagnetic steel sheet 40. As the non-oriented electromagnetic steel sheet, a non-oriented electrical steel strip according to JIS C2552:2014 can be used. However, a directional electromagnetic steel sheet may be used as the electromagnetic steel sheet 40 instead of the non-oriented electromagnetic steel sheet. In this case, as the directional electromagnetic steel sheet, a directional electrical steel strip according to JIS C2553:2012 can be used.
[0027] In order to improve the workability of the electromagnetic steel sheet 40 and the iron loss of the stator core 21 (hereinafter, sometimes simply referred to as the "laminated core"), both sides of the electromagnetic steel sheet 40 are covered with an insulating coating. Examples of the material constituting the insulating coating include (1) an inorganic compound, (2) an organic resin, and (3) a mixture of an inorganic compound and an organic resin. Among these, when the insulating coating is (1) an inorganic compound or (3) a mixture of an inorganic compound and an organic resin, the deterioration of the magnetic properties due to the shrinkage at the time of hardening of each adhesive portion can be significantly suppressed. Examples of the inorganic compound include (1) a complex of dichromate and boric acid, and (2) a complex of phosphate and silica. Examples of the organic resin include an epoxy resin, an acrylic resin, an acrylic styrene resin, a polyester resin, a silicon resin, and a fluorine resin.
[0028] In order to ensure the insulating performance between the laminated magnetic steel sheets 40, the upper limit of the average thickness of the insulating coating (average thickness per one side of the magnetic steel sheets 40) is preferably 1.5 μm, and more preferably 1.2 μm. On the other hand, as the insulating coating becomes thicker, the insulating effect becomes saturated. Also, as the insulating coating becomes thicker, the proportion of the electromagnetic steel sheets 40 in the laminated core decreases, and the performance of the laminated core decreases. Therefore, it is preferable that the insulating coating is thin as long as the insulating performance can be ensured. The lower limit of the average thickness of the insulating coating (thickness per one side of the electromagnetic steel sheets 40) is 0.3 μm, and more preferably 0.5 μm. The average thickness of the insulating coating can be, for example, 0.8 μm within the above upper and lower limit range. The average thickness of the insulating coating is the average value for the entire laminated core. The thickness of the insulating coating hardly changes depending on the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness of the insulating coating can be determined by the value measured at the upper end position of the laminated core.
[0029] As the sheet thickness of the electromagnetic steel sheet 40 becomes thinner, the iron loss improvement effect gradually saturates. Also, as the electromagnetic steel sheet 40 becomes thinner, the manufacturing cost of the electromagnetic steel sheet 40 increases. Therefore, in consideration of the iron loss improvement effect and manufacturing cost, it is preferable that the thickness of the electromagnetic steel sheet 40 be 0.10 mm or more. On the other hand, if the electromagnetic steel sheet 40 is too thick, it becomes difficult to perform the press punching operation of the electromagnetic steel sheet 40. Therefore, in consideration of the press punching operation of the electromagnetic steel sheet 40, it is preferable that the thickness of the electromagnetic steel sheet 40 is 0.65 mm or less. Note that the thickness of the electromagnetic steel sheet 40 includes the thickness of the insulating coating. The average thickness of each electromagnetic steel sheet 40 is the average thickness of the entire laminated core. The thickness of each electromagnetic steel sheet 40 hardly changes depending on the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness of each electromagnetic steel sheet 40 can be determined by the value measured at the upper end position of the laminated core.
[0030] The multiple electromagnetic steel sheets 40 forming the stator core 21 are stacked via adhesive parts 41 arranged, for example, at multiple points. Each adhesive part 41 is formed of a hardened adhesive without being separated. For example, a thermosetting adhesive by polymerization bonding is used for the adhesive parts 41. The adhesive for forming the adhesive parts 41 can be an adhesive that has oily surface adhesion and contains any of (1) an acrylic resin, (2) an epoxy resin, or (3) an acrylic resin and an epoxy resin.
[0031] As the adhesive for forming the adhesive portion 41, in addition to a thermosetting adhesive, a radical polymerization type adhesive or the like can be used, and from the viewpoint of productivity, it is desirable to use a room temperature curing adhesive. A room temperature curing adhesive cures at 20°C to 30°C. An acrylic adhesive is preferable as a room temperature curing type (room temperature adhesion type) adhesive. A representative acrylic adhesive is SGA (Second Generation Acrylic Adhesive). As long as the effect of the present invention is not impaired, any of anaerobic adhesives, instant adhesives, and elastomer-containing acrylic adhesives can be used. Note that the adhesive referred to here refers to the state before curing, and becomes the adhesive portion 41 after the adhesive has cured.
[0032] The average tensile modulus of the adhesive portion 41 at room temperature (20°C to 30°C) is set to be within the range of 1500MPa to 4500MPa. If the average tensile modulus of the adhesive portion 41 is less than 1500MPa, the rigidity of the laminated core is reduced. Therefore, the lower limit of the average tensile modulus of the adhesive portion 41 is set to 1500MPa, more preferably 1800MPa. On the other hand, if the average tensile modulus of the adhesive portion 41 exceeds 4500MPa, the stress strain applied to the electromagnetic steel sheet 40 increases, and the core magnetism is deteriorated. Therefore, the upper limit of the average tensile modulus of the adhesive portion 41 is set to 4500MPa, more preferably 3650MPa. The average tensile modulus of each adhesive portion 41 can be adjusted by changing one or both of the heating and pressing conditions and the type of hardener applied during bonding. The average tensile elastic modulus E is measured by a resonance method, specifically, in accordance with JIS R 1602:1995.
[0033] More specifically, first, a sample for measurement (not shown) is produced. This sample is obtained by bonding two electromagnetic steel sheets 40 with the adhesive to be measured and curing the adhesive to form a bonded joint 41. If the adhesive is a thermosetting type, this curing is performed by heating and pressing under heating and pressing conditions for actual operation. On the other hand, if the adhesive is a room temperature curing type, this is performed by pressing at room temperature. The tensile modulus of elasticity of this sample is then measured by a resonance method. The method for measuring the tensile modulus of elasticity by the resonance method is performed in accordance with JIS R 1602:1995, as described above. The tensile modulus of elasticity of the adhesive portion 41 alone is then found by subtracting the influence of the magnetic steel sheet 40 itself from the tensile modulus of elasticity (measured value) of the sample through calculation.
[0034] The tensile modulus thus determined from the samples is equal to the average value for the entire laminated core, and this value is regarded as the average tensile modulus. The composition is set so that the average tensile modulus is almost the same for the lamination position along the lamination direction and the circumferential position around the central axis of the laminated core. Therefore, the average tensile modulus can be determined as the value of the cured adhesive part 41 at the upper end of the laminated core.
[0035] A method of bonding between multiple electromagnetic steel sheets 40 can be adopted in which an adhesive is applied to the lower surface (one surface) of the electromagnetic steel sheets 40, the sheets are then stacked, and either or both of them are heated and pressed to harden, thereby forming adhesive joints 41. Note that any means may be used for heating, such as a means for heating stator core 21 in a high-temperature tank or electric furnace, or a method for heating stator core 21 by directly passing electricity through it. On the other hand, when a room-temperature-curing adhesive is used, the sheets are bonded only by pressing without heating.
[0036] In order to obtain a stable and sufficient adhesive strength, the thickness of the adhesive portion 41 is preferably 1 μm or more. On the other hand, if the thickness of the adhesive portion 41 exceeds 100 μm, the adhesive strength becomes saturated. Also, as the adhesive portion 41 becomes thicker, the space factor decreases, and the magnetic properties such as the core loss of the laminated core deteriorate. Therefore, the thickness of the adhesive portion 41 is preferably set to 1 μm or more and 100 μm or less, and more preferably 1 μm or more and 10 μm or less. In the above, the thickness of the adhesive portion 41 means the average thickness of the adhesive portion 41 .
[0037] It is more preferable that the average thickness of the adhesive portion 41 is 1.0 μm or more and 3.0 μm or less. If the average thickness of the adhesive portion 41 is less than 1.0 μm, sufficient adhesive strength cannot be ensured as described above. Therefore, the lower limit of the average thickness of the adhesive portion 41 is set to 1.0 μm, more preferably 1.2 μm. Conversely, if the average thickness of the adhesive portion 41 exceeds 3.0 μm and becomes too thick, problems such as a significant increase in the amount of distortion of the electromagnetic steel sheet 40 due to shrinkage during thermal curing occur. Therefore, the upper limit of the average thickness of the adhesive portion 41 is set to 3.0 μm, more preferably 2.6 μm.
[0038] The average thickness of the adhesive portion 41 is the average value for the entire laminated core. The average thickness of the adhesive portion 41 hardly changes depending on the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness of the adhesive portion 41 can be determined by averaging values measured at 10 or more points in the circumferential direction at the upper end position of the laminated core. The average thickness of the adhesive portion 41 can be adjusted, for example, by changing the amount of adhesive applied.
[0039] Fig. 3 shows an example of a formation pattern of the adhesive portion 41. In Fig. 3, two formation patterns 41A and 41B are shown together in one figure, with a dashed dotted line as the boundary. When formation pattern 41A is adopted, the entire surface of the electromagnetic steel sheet 40 is formed in this coating pattern. On the other hand, when formation pattern 41B is adopted, the entire surface of the electromagnetic steel sheet 40 is formed in this coating pattern. First, in the case of forming pattern 41A, adhesive portions 41 are formed so that the average area ratio of core back portion 22 and the average area ratio of teeth portion 23 are equal at each position in the stacking direction of the laminated core, but the components of the adhesives used are different. A plurality of circular dot-like adhesive portions 41 are annularly arranged in core back portion 22. Each adhesive portion 41 on core back portion 22 is arranged to overlap an imaginary straight line EL1 connecting the widthwise center position of each tooth portion 23 and the central axis O of electromagnetic steel sheet 40.
[0040] On the other hand, in each tooth portion 23, two adhesive portions 41 are arranged side by side so as to overlap with the imaginary straight line EL1. The diameter dimension of the adhesive portion 41 in the core back portion 22 is larger than the diameter dimension of the adhesive portion 41 in the tooth portion 23. Therefore, the number of adhesive portions 41 in the core back portion 22 is smaller than the number of adhesive portions 41 in the tooth portion 23, but the area ratios are the same. In other words, the ratio of the sum of the areas of the adhesive portions 41 on the core back portion 22 to the total area of the core back portion 22 is the same as the ratio of the sum of the areas of the adhesive portions 41 on the tooth portion 23 to the total area of the tooth portion 23.
[0041] When considering the total adhesive strength between overlapping electromagnetic steel sheets 40 as a partial strength divided into core back portion 22 and teeth portion 23, if the same adhesive is used, the partial adhesive strength in core back portion 22 and the partial adhesive strength in teeth portion 23 will be the same. However, in this forming pattern 41A, the adhesive strength of the adhesive used to form adhesive portion 41 formed in core back portion 22 is higher than the adhesive strength of the adhesive used to form adhesive portion 41 formed in teeth portion 23.
[0042] As a result, between each of the electromagnetic steel sheets 40, the average adhesive strength per unit area in the teeth portion 23 due to each adhesive portion 41 is lower than the average adhesive strength per unit area in the core back portion 22. More specifically, the average value of the adhesive strength ratio obtained by dividing the partial adhesive strength per unit area in the teeth portion 23 by the partial adhesive strength per unit area in the core back portion 22 is within a range of 0.1 or more and less than 1.0. The upper limit of this average adhesive strength ratio is preferably 0.8, and more preferably 0.6. The lower limit of the average adhesive strength ratio is preferably 0.15, and more preferably 0.2.
[0043] Next, in the case of the forming pattern 41B shown in FIG. 3, the average value of the partial adhesive strength or the average value of the area ratio of the core back portion 22 and the teeth portion 23 differ from each other at each position in the stacking direction of the laminated core. Specifically, when comparing the average values of the partial adhesive strengths, the average value S1 of the partial adhesive strengths in the teeth portion 23 is 1 to 15 MPa, and the average value S2 of the partial adhesive strengths in the core-back portion 22 is 15 to 50 MPa. The average value S1 is lower than the average value S2. The lower limit of the average value S1 is preferably 2 MPa, and more preferably 3 MPa. The upper limit of the average value S1 is preferably 10 MPa, and more preferably 8 MPa. Meanwhile, the lower limit of the average value S2 is preferably 20 MPa, and more preferably 30 MPa. The upper limit of the average value S2 is preferably 45 MPa, and more preferably 40 MPa. However, the fact remains that the average value S1 is lower than the average value S2.
[0044] On the other hand, when comparing the average area ratios, the average area ratio A1 of each bonding portion 41 in the teeth portion 23 is 10 to 50%, and the average area ratio A2 of each bonding portion 41 in the core-back portion 22 is 50 to 100%. The average value A1 is lower than the average value A2. The average adhesive strength per unit area of each bonding portion 41 is 5 to 50 MPa, which is common to each position of the teeth portion 23 and the core-back portion 22. The lower limit of the average value A1 is preferably 10%. The upper limit of the average value A1 is preferably 30%, more preferably 20%. Meanwhile, the lower limit of the average value A2 is preferably 60%, more preferably 70%. The upper limit of the average value A2 is preferably 90%, more preferably 80%. However, the fact remains that the average value A1 is lower than the average value A2.
[0045] In this way, by specifying the average partial adhesive strength or the average area ratio between the core back portion 22 and the teeth portion 23 as described above, it is possible to make the average adhesive strength per unit area of each adhesive portion 41 in the teeth portion 23 lower than the average adhesive strength per unit area in the core back portion 22.
[0046] Regarding the arrangement of the adhesive portions 41, a plurality of circular dot-like adhesive portions 41 are arranged in an annular manner in the core back portion 22. Each adhesive portion 41 of the core back portion 22 is arranged to overlap an imaginary straight line EL2 that connects the widthwise center position of each tooth portion 23 and the central axis O of the electromagnetic steel sheet 40.
[0047] On the other hand, in the teeth portion 23, one adhesive portion 41 per one tooth portion 23 is arranged to overlap on the imaginary straight line EL2. The diameter dimension of the adhesive portion 41 in the core back portion 22 is larger than the diameter dimension of the adhesive portion 41 in the teeth portion 23. As a result, at each position in the stacking direction of the laminated core, the average value of the partial adhesive strength is kept lower in the teeth portion 23 than in the core back portion 22. In other words, at each position in the stacking direction of the laminated core, the average value of the area ratio is kept lower in the teeth portion 23 than in the core back portion 22. As a result, between each of the electromagnetic steel sheets 40 , the average adhesive strength per unit area at each adhesive portion 41 in the teeth portion 23 is lower than the average adhesive strength per unit area in the core back portion 22 .
[0048] In this embodiment, the multiple electromagnetic steel sheets forming rotor core 31 are fixed to one another by crimps 42 (dowels) shown in Fig. 1. However, the multiple electromagnetic steel sheets forming rotor core 31 may also have a laminated structure fixed by an adhesive, similar to stator core 21. Furthermore, laminated cores such as the stator core 21 and the rotor core 31 may be formed by so-called rotational lamination. EXAMPLES
[0049] The above-mentioned stator core 21 was manufactured using the manufacturing apparatus 100 shown in FIG. 4 while changing various manufacturing conditions. First, a description will be given of the manufacturing apparatus 100. In the manufacturing apparatus 100, while an electromagnetic steel sheet P is sent out from a coil C (hoop) in the direction of an arrow F, it is punched multiple times using dies arranged at each stage to gradually form the shape of the electromagnetic steel sheet 40, an adhesive is applied to the underside of the electromagnetic steel sheet 40, the punched electromagnetic steel sheets 40 are stacked, and the temperature is raised while they are pressure-bonded to form each bonding portion 41.
[0050] As shown in Figure 4, the manufacturing apparatus 100 includes a first-stage punching station 110 located closest to the coil C, a second-stage punching station 120 located adjacent to the punching station 110 on the downstream side along the conveying direction of the electromagnetic steel sheet P, and an adhesive application station 130 located adjacent to the punching station 120 on the further downstream side. The punching station 110 includes a female die 111 arranged below the electromagnetic steel sheet P and a male die 112 arranged above the electromagnetic steel sheet P. The punching station 120 includes a female die 121 arranged below the electromagnetic steel sheet P and a male die 122 arranged above the electromagnetic steel sheet P. Depending on the planar design of the motor, the stamping stations may be located even more.
[0051] The adhesive application station 130 includes an applicator 131 having a plurality of injectors arranged according to an adhesive application pattern. That is, each injector is arranged at a position corresponding to the formation position of each adhesive portion 41 shown in FIG. 3. The nozzle diameter of each injector is different from each other according to the size of the adhesive portion 41 to be formed. In addition, in the case of the formation pattern 41A, an adhesive flow path leading to an injector that applies adhesive to the core back portion 22 and an adhesive flow path leading to another injector that applies adhesive to the teeth portion 23 may be separated. In this case, the chemical components of the adhesive to be applied to the core back portion 22 and the chemical components of the adhesive to be applied to the teeth portion 23 can be separated.
[0052] Note that, instead of the above-described configuration in which multiple types of adhesives are applied simultaneously by one adhesive application station 130, multiple (e.g., two) adhesive application stations 130 may be provided to apply different types of adhesive. In this case, the first adhesive application station 130 applies a first type of adhesive to one of the teeth portion 23 and the core back portion 22, and the second adhesive application station 130 applies a second type of adhesive to the other.
[0053] The manufacturing apparatus 100 further includes a lamination station 140 located downstream of the adhesive application station 130. The lamination station 140 includes a heating device 141, a female peripheral punching die 142, a heat insulating member 143, a male peripheral punching die 144, and a spring 145. The heating device 141, the outer periphery punching female die 142, and the heat insulating member 143 are disposed below the electromagnetic steel sheet P. On the other hand, the outer periphery punching male die 144 and the spring 145 are disposed above the electromagnetic steel sheet P. The reference numeral 21 denotes a stator core.
[0054] In the manufacturing apparatus 100 in FIG. 4 having the configuration described above, first, the electromagnetic steel sheet P is sequentially sent out from the coil C in the direction of the arrow F. Then, the electromagnetic steel sheet P is subjected to a punching process by the punching station 110. Next, the electromagnetic steel sheet P is subjected to a punching process by the punching station 120. Through these punching processes, the electromagnetic steel sheet P is given the shape of the electromagnetic steel sheet 40 having the core back portion 22 and the multiple teeth portions 23 shown in FIG. 3. However, since the electromagnetic steel sheet P is not completely punched out at this point, it proceeds to the next process along the direction of the arrow F. In the adhesive application station 130 in the next process, the adhesive supplied from each of the injectors of the applicator 131 is applied in dots. At that time, the amount or type of adhesive applied is different between the core back portion 22 and the teeth portion 23.
[0055] Finally, the electromagnetic steel sheets P are sent to a lamination station 140, where they are punched out by a peripheral punching male die 144 and laminated with high precision. During this lamination, the electromagnetic steel sheets 40 receive a constant pressure from a spring 145. By sequentially repeating the punching step, adhesive application step, and lamination step as described above, a predetermined number of electromagnetic steel sheets 40 can be stacked. Furthermore, the laminated core formed by stacking the electromagnetic steel sheets 40 in this manner is heated by a heating device 141 to a temperature of, for example, 200° C. in the case of thermosetting adhesive. This heating hardens the adhesive, forming the adhesive portion 41. In the case of a room temperature curing adhesive, the adhesive hardens over time, forming the adhesive portion 41. Through the above steps, the stator core 21 is completed.
[0056] Stator cores 21 shown in Nos. 1 to 13 in Tables 1A and 1B were manufactured using the manufacturing apparatus 100 described above. In addition, for comparative example manufacturing, stator core 21 shown in No. 14 was also manufactured using another apparatus. First, the thickness of the hoop (coil C) was set to 0.25 mm. An insulating coating solution containing metal phosphate and acrylic resin emulsion was applied to the hoop and baked at 300°C to form an insulating coating of 0.8 μm on one side. Next, a hoop was formed by punching out a single-plate core (electromagnetic steel sheet 40) using the manufacturing apparatus 100, which had a ring shape with an outer diameter of 300 mm and an inner diameter of 240 mm and had 18 rectangular teeth portions, each 30 mm long and 15 mm wide, on the inner diameter side. Next, while the punched single-layer cores were being fed in sequence, the adhesive was applied in dot form to each of the positions shown in FIG. 3 (except for Comparative Example No. 14).
[0057] The chemical compositions of the electromagnetic steel sheets 40 used in manufacturing each stator core 21 were unified as follows. Note that the values of each component are all expressed in mass %. Si: 3.1% Al: 0.7% Mn: 0.3% Remainder: Fe and impurities
[0058] [Table 1A]
[0059] [Table 1B]
[0060] On the other hand, adhesives selected from the following and appropriately combined were used to form each adhesive portion 41. Specific combinations are shown in Table 1A. Chloroprene rubber adhesive (adhesive strength: 2MPa) Cyanoacrylate A adhesive (adhesive strength: 5MPa) Anaerobic adhesive (bonding strength: 15MPa) Cyanoacrylate B adhesive (adhesive strength: 24MPa) Epoxy A adhesive (bonding strength: 32MPa) Epoxy B adhesive (bonding strength: 42MPa) Epoxy C adhesive (bonding strength: 64MPa) SGA (adhesive strength: 48MPa)
[0061] In addition, in all of the examples in Tables 1A and 1B, the area ratio of the adhesive portion 41 in the teeth portion 23 is set to be equal to the area ratio of the adhesive portion 41 in the core back portion 22. Therefore, as shown in Table 1A, the adhesive strength ratio obtained by dividing the partial adhesive strength in the teeth portion 23 by the partial adhesive strength in the core back portion 22 is equal to the adhesive strength ratio (above, excluding Comparative Example No. 14). Note that the partial adhesive strength refers to the adhesive strength (adhesive strength) of the portion of the teeth portion 23 alone or the portion of the core back portion 22 alone. The magnetic steel sheets 40 after the adhesive was applied were stacked, and then heated and hardened while being pressed with a predetermined pressure to form each adhesive portion 41. The same process was repeated for 130 single plate cores to manufacture a laminated core (stator core 21).
[0062] On the other hand, in the stator core 21 of No. 14, no adhesive was used to bond the electromagnetic steel sheets 40 together, and the electromagnetic steel sheets 40 were mechanically joined together by crimped portions. These crimped portions were formed in both the core back portion 22 and the teeth portion 23. In addition, the size of the crimped portion in the teeth portion 23 was made smaller than the size of the crimped portion in the core back portion 22. This allowed the partial bond strength, which is the average bond strength per unit area in the teeth portion 23, to be adjusted to be lower than the partial bond strength, which is the average bond strength per unit area in the core back portion 22.
[0063] The stiffness (mechanical strength) of each of the laminated cores No. 1 to 14 manufactured by the method described above was evaluated. The mechanical strength was evaluated by a hammering test. In the "Stiffness of Laminated Core" column of Table 1B, "Excellent" indicates that high mechanical strength is ensured, "Good" indicates that sufficient mechanical strength is ensured, and "Poor" indicates that the minimum required mechanical strength is insufficient. Here, "Excellent" is "1," "Good" is "2," "Fair" is "3," and "Poor" is "4" or "5."
[0064] <Hit test (noise evaluation)> The outer peripheral end of the core back portion 22 of the laminated core was vibrated in the radial direction by an impact hammer, and a modal analysis of vibration was performed using the tips of the teeth portion 23 and the center portion of the core back portion 22 in the axial direction at 180° to the vibration source as measurement points. Also, when the radial center portion of the core back portion 22 was vibrated in the axial direction by an impact hammer, a modal analysis of vibration was performed using the tips of the teeth portion 23 and the center portion of the core back portion 22 in the axial direction at 180° to the vibration source as measurement points.
[0065] The evaluation (judgment) was performed according to the following criteria. The smaller the value, the more vibration is suppressed and the higher the mechanical strength is. 1 (Excellent): Only one or two vibrational peaks are detected. 2 (Good): Several vibration peaks are detected. 3 (Acceptable): Depending on the vibration direction, 10 or more vibration peaks are detected. 4 (Not acceptable): A main peak is present, but 10 or more vibrational peaks are detected. 5 (Fail): No main peak, and 10 or more vibration peaks are detected.
[0066] Furthermore, the magnetic properties of the laminated core were also evaluated. The magnetic properties were evaluated by measuring the iron loss using a rotational iron loss simulator (not shown) with a rotor-shaped detector with a diameter of 239.5 mm. In the "Magnetic Properties of Teeth" column of Table 1B, "Excellent" indicates that extremely high magnetic properties have been ensured. "Good" indicates that high magnetic properties have been ensured. "Fair" indicates that sufficient magnetic properties have been ensured. "Poor" indicates that the magnetic properties are lower than the minimum required.
[0067] First, the iron loss value measured at a magnetic flux density of 1.5 Tesla for the electromagnetic steel sheet 40 before bonding was obtained as a reference value. Next, the iron loss of each laminated core was measured at the same magnetic flux density of 1.5 Tesla. The iron loss of each laminated core was then divided by the reference value and expressed as 100%, to obtain the increase rate. For example, No. 1 in Table 1B has an iron loss increase rate of 105%, which indicates that the iron loss increased by 5% compared to the reference value. If the iron loss increase rate obtained in this way was 5% or less (the value in the table is 105% or less), it was rated as "excellent", if it was more than 5% and less than 10% (the value in the table is more than 105% and less than 110%), it was rated as "good", if it was more than 10% and less than 20% (the value in the table is more than 110% and less than 120%), it was rated as "passable", and if it was more than 120% (the value in the table is more than 120%), it was rated as "unacceptable".
[0068] As shown in Tables 1A and 1B, in the comparative example shown in No. 9, the partial adhesive strength at the teeth portion 23 was significantly higher than the partial strength at the core back portion 22, so the magnetic properties of the teeth portion 23 were degraded. In addition, the partial adhesive strength at the core back portion 22 was too low, so the rigidity of the laminated core was also degraded. In the comparative examples shown as Nos. 10 to 12, the partial adhesive strength of the teeth portion 23 was higher than the partial strength of the core-back portion 22, so that the magnetic properties of the teeth portion 23 were degraded. In addition, in the comparative example shown as No. 14 in which a crimped portion was used, a compressive force was applied to the teeth 23 due to the formation of the crimped portion, resulting in a significant deterioration in the magnetic properties. On the other hand, in the invention examples Nos. 1 to 8 and 13, the laminated core had high rigidity (mechanical strength) and also had high magnetic properties, and it was confirmed that they had the desired performance.
[0069] The relationship between the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position shown in Table 1A is shown in Fig. 5. In Fig. 5, comparative examples Nos. 9 to 12 are located below boundary line B1, where the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position are equal. No. 14 is located above boundary line B1, but because the magnetic steel sheets 40 are joined by crimping rather than by adhesion, as described above, desired characteristics, particularly magnetic characteristics, were not obtained.
[0070] Boundary line B2 indicates the condition where the adhesive strength ratio is 0.1. Example No. 13, which is located to the left of boundary line B2 on the paper, was rated "acceptable" for both the rigidity and magnetic properties of the laminated core, but did not achieve "excellent" because the bonding strength of the teeth portion 23 was low and there were even cases where the rigidity of the laminated core was slightly insufficient. On the other hand, examples No. 1 to 8 of the invention achieved "excellent" or similar results for either the rigidity or magnetic properties of the laminated core. From these results, it can be said that it is more preferable for the adhesive strength ratio to be less than 1.0 and at least 0.1.
[0071] Next, the manufacturing apparatus 100 was used to manufacture the stator cores 21 shown in No. 15 to No. 29 in Tables 2A and 2B. In this example, although the adhesive used was changed for each case, the adhesive applied to the teeth portion 23 was the same as the adhesive applied to the core back portion 22. Therefore, the adhesive strength ratios were all standardized to 1.00. On the other hand, regarding the area ratio, the amount of adhesive applied to the teeth portion 23 was made different from the amount of adhesive applied to the core back portion 22, and as a result, the area ratio ratio was changed for each case. In Table 2B, the thresholds for "excellent," "good," "fair," and "poor" regarding the rigidity of the laminated core are as described in Table 1B. Similarly, the thresholds for "excellent," "good," "fair," and "poor" regarding the magnetic properties of the teeth are as described in Table 1B.
[0072] [Table 2A]
[0073] [Table 2B]
[0074] In the comparative examples Nos. 23 to 25 shown in Tables 2A and 2B, the partial adhesive strength of teeth portion 23 was higher than the partial strength of core back portion 22, resulting in degraded magnetic properties of teeth portion 23. The relationship between the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position shown in Table 2A is shown in Fig. 6. In Fig. 6, comparative examples Nos. 23 to 25 are located below boundary line B3 where the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position are equal.
[0075] On the other hand, as shown in Table 2B, in the invention examples Nos. 15 to 22 and 26 to 29, the laminated core had high rigidity (mechanical strength) and also had high magnetic properties, and was confirmed to have the desired performance. In addition, examples 17-20 and 27 enclosed by boundary line B4 forming a rectangular frame were awarded "excellent" for both the rigidity and magnetic properties of the laminated core. From these results, it was found that it is more preferable that the average value S1 of the partial adhesive strength in the teeth portion 23 is 3-15 MPa, the average value S2 of the partial adhesive strength in the core-back portion 22 is 15-50 MPa, and the average value S1 is lower than the average value S2.
[0076] Next, using the manufacturing apparatus 100, the stator cores 21 shown in Nos. 30 to 47 in Tables 3A and 3B were manufactured. In Table 3B, the thresholds for "excellent," "good," "fair," and "poor" regarding the rigidity of the laminated core are as described in Table 1B. Similarly, the thresholds for "excellent," "good," "fair," and "poor" regarding the magnetic properties of the teeth are as described in Table 1B.
[0077] In No. 30 to No. 46, although the adhesive used was different for each case, the adhesive applied to the teeth portion 23 and the adhesive applied to the core back portion 22 were the same (adhesive having the same chemical components). Therefore, the adhesive strength ratios were all standardized to 1.00. In addition, with regard to the area ratio, the amount of adhesive applied to the teeth portion 23 was different from the amount of adhesive applied to the core back portion 22, and as a result, the area ratio ratio was different for each case.
[0078] On the other hand, in No. 47, the adhesive applied to the teeth portion 23 and the adhesive applied to the core back portion 22 were different. Moreover, in No. 47, the combination of the two adhesives was selected so that the adhesive strength of the adhesive in the teeth portion 23 was lower than the adhesive strength of the adhesive in the core back portion 22. In addition, regarding the area ratio, the amount of adhesive applied to the teeth portion 23 was made smaller than the amount of adhesive applied to the core back portion 22. As a result, the area ratio of the teeth portion 23 was made smaller than the area ratio of the core back portion 22.
[0079] [Table 3A]
[0080] [Table 3B]
[0081] As a result, in the comparative examples No. 40 to 42 shown in Tables 3A and 3B, the partial adhesive strength of the teeth portion 23 was higher than the partial strength of the core back portion 22, resulting in degraded magnetic properties of the teeth portion 23. On the other hand, as shown in Tables 3A and 3B, inventive examples Nos. 30 to 39 and 43 to 47, the laminated core had high rigidity (mechanical strength) and also had high magnetic properties, and was confirmed to have the desired performance.
[0082] The relationship between the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position shown in Table 3A is shown in Fig. 7. In Fig. 7, comparative examples Nos. 40 to 42 are located below boundary line B5 where the partial adhesive strength at the teeth position and the partial adhesive strength at the core back position are equal.
[0083] Furthermore, the relationship between the area ratio at the tooth portion position and the area ratio at the core back portion position shown in Table 3A is shown in FIG. In Fig. 8, examples 30 to 37 enclosed by boundary line B6 forming a rectangular frame achieved "excellent" or similar results in both rigidity and magnetic properties of the laminated core. From these results, it was found that it is more preferable that the average value A1 of the area ratio of each of the bonding portions in the teeth portion 23 is 10 to 50%, and the average value A2 of the area ratio of each of the bonding portions in the core back portion 22 is 50 to 100%, and the average value A1 is lower than the average value A2.
[0084] An embodiment of the present invention and examples have been described above. However, the technical scope of the present invention is not limited to the above embodiment and examples, and various modifications can be made without departing from the spirit of the present invention. For example, the shape of the stator core 21 is not limited to the form shown in the above embodiment. Specifically, the outer diameter and inner diameter dimensions of the stator core 21, the lamination thickness, the number of slots, the circumferential and radial dimensional ratios of the teeth portion 23, and the radial dimensional ratios of the teeth portion 23 and the core back portion 22 can be designed as desired according to the characteristics of the rotating electric machine. In the rotor 30 in the above embodiment, a pair of permanent magnets 32 form one magnetic pole, but the present invention is not limited to this embodiment. For example, one permanent magnet 32 may form one magnetic pole, or three or more permanent magnets 32 may form one magnetic pole.
[0085] In the above embodiment, a permanent magnet field type motor has been used as an example of the rotating motor 10, but the structure of the rotating motor 10 is not limited to this, as exemplified below, and various known structures not exemplified below can also be adopted. In the above embodiment, a permanent magnet field type motor has been described as an example of the rotating electric machine 10, but the present invention is not limited to this. For example, the rotating electric machine 10 may be a reluctance type motor or an electromagnetic field type motor (wound field type motor). In the above embodiment, a synchronous motor is used as an example of an AC motor, but the present invention is not limited to this. For example, the rotating electric machine 10 may be an induction motor. In the above embodiment, an AC motor has been described as an example of the rotating electric machine 10, but the present invention is not limited to this. For example, the rotating electric machine 10 may be a DC motor. In the above embodiment, an electric motor has been taken as an example of the rotating electric machine 10, but the present invention is not limited to this. For example, the rotating electric machine 10 may be a generator.
[0086] In addition, within the scope of the invention, the components in the above-described embodiments may be replaced with well-known components, and the above-described modified examples may be combined as appropriate. [Industrial Applicability]
[0087] According to the present invention, it is possible to provide an adhesive laminated core for a stator having an adhesive structure that enhances mechanical strength without adversely affecting magnetic properties, and a rotating electric machine having the adhesive laminated core for a stator. Therefore, the present invention has great industrial applicability. [Explanation of symbols]
[0088] 10 Rotating Electric Machine 21 Stator adhesive laminated core 22 Core back section 23 Teeth 40 Electrical steel sheet 41 Adhesive part
Claims
1. The magnetic core comprises a plurality of electromagnetic steel sheets each having a core back portion and a teeth portion and stacked coaxially, and a plurality of bonding portions bonding the electromagnetic steel sheets together at the core back portion and the teeth portion, Between the electromagnetic steel sheets, a partial adhesive strength per unit area of each adhesive portion in the teeth portion at a room temperature of 20°C to 30°C is lower than a partial adhesive strength per unit area of each adhesive portion in the core back portion, the adhesive portion in the core back portion and the adhesive portion in the teeth portion are made of adhesives having different chemical components, an average value of an adhesive strength ratio obtained by dividing the partial adhesive strength of the teeth portion by the partial adhesive strength of the core back portion at a normal temperature of 20° C. to 30° C. is within a range of 0.1 or more and less than 1.0; 1. A bonded laminated core for a stator, comprising:
2. The adhesive portions are arranged on both the teeth and the core back portion so as to overlap with each imaginary straight line connecting a widthwise center position of each of the teeth and a central axis of the electromagnetic steel sheet.
2. The adhesive laminated core for a stator according to claim 1.
3. The adhesive portion is provided on each of the teeth portions, The adhesive portion is provided at all positions of the core back portion adjacent to the radial outside of each of the teeth portions.
2. The adhesive laminated core for a stator according to claim 1.
4. The average value S1 of the partial adhesive strength in the teeth portion is 1 to 15 MPa, the average value S2 of the partial adhesive strength in the core-back portion is 15 to 50 MPa, and the average value S1 is lower than the average value S2; 4. The adhesive laminated core for a stator according to claim 1, wherein the adhesive laminated core for a stator is a laminated core.
5. The average thickness of each of the adhesive joints is 1.0 μm to 3.0 μm.
4. The adhesive laminated core for a stator according to claim 1, wherein the adhesive laminated core for a stator is a laminated core.
6. The average tensile modulus E of each of the adhesive joints is 1500 MPa to 4500 MPa.
4. The adhesive laminated core for a stator according to claim 1, wherein the adhesive laminated core for a stator is a laminated core.
7. Each of the adhesive parts is an acrylic adhesive of room temperature adhesive type containing SGA made of an elastomer-containing acrylic adhesive.
4. The adhesive laminated core for a stator according to claim 1, wherein the adhesive laminated core for a stator is a laminated core.
8. A rotating electric machine comprising the adhesive laminated core for a stator according to any one of claims 1 to 3.
Citation Information
Patent Citations
Stator and motor employing the stator
JP2002125341A
Direct drive motor
JP2015012756A
Method of manufacturing motor and motor core
JP2016171652A
Manufacturing method and manufacturing apparatus of laminate steel sheet
JP2018038119A